PIV-based dynamic model of EHD volume force produced by a surface dielectric barrier discharge - Benard,N; Laizet,S; Moreau,E (American Institute of Aeronautics and Astronautics, 2017)
In this paper, an experimental measurement of the flow produced by a surface DBD plasma actuator has been conducted. One original aspect of these measurements by particle image velocimetry is the high acquisition rate for a PIV system (20 kHz). By using these highly-resolved flow measurements, the fluid flow velocity is used to estimate the spatial and temporal evolution of the EHD volume force. A reduced order model of this force has been constructed by proper orthogonal decomposition. Based on the analysis of the time-resolved expansion coefficients and their associated spatial modes, it is shown that the volume force can be reconstructed by using a limited number of POD modes (6 modes). This spatial and temporal filtering of the force fields remains faithful to the original data and it will help in view of an implementation of such a source term in a numerical solver. The resulting dynamic model shows an alternation of positive and negative volume forces. The strong positive EHD force developing in the glow regime of the DBD plasma discharge is visualized in a time-resolved manner. This positive force is immediately followed by a strong negative volume force probably caused by the local flow deceleration.